2008
DOI: 10.1016/j.aquaculture.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Feed demand behavior in sea bass juveniles: Effects on individual specific growth rate variation and health (inter-individual and inter-group variation)

Abstract: Feeding motivation is one major indicator of fish welfare and an investigation on the link between feed demand, growth and physiological variables in sea bass juveniles was developed. A computerized ondemand feeding system coupled with a PIT tag monitoring device was used to continuously record for 219 days the triggering activity of 150 individuals (initial average body weight 131.6 ± 1.80 g and coefficient of variation 16.8%). Each group was held in 400 l tanks at 22.2 ± 1.5 °C and light regime was 16:8 LD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
49
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 46 publications
11
49
1
Order By: Relevance
“…Trigger actuations were recorded continuously throughout the experimental period and the identity of the triggering fish was determined in approximately 90% of the cases (the remaining 10% without fish ID was not included in the analyses). The number of trigger actuations per individual was used to calculate the proportional contribution of an individual fish to the total number of trigger actuations within its group over the entire experimental period and to assign the individual to one of the categories: high-triggering (< 25% actuations, HTF), low-triggering (> 25%, LTF) and zero-triggering (0%, ZTF) fish (Coves et al 2006;Millot et al 2008;Millot and Bégout 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trigger actuations were recorded continuously throughout the experimental period and the identity of the triggering fish was determined in approximately 90% of the cases (the remaining 10% without fish ID was not included in the analyses). The number of trigger actuations per individual was used to calculate the proportional contribution of an individual fish to the total number of trigger actuations within its group over the entire experimental period and to assign the individual to one of the categories: high-triggering (< 25% actuations, HTF), low-triggering (> 25%, LTF) and zero-triggering (0%, ZTF) fish (Coves et al 2006;Millot et al 2008;Millot and Bégout 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies with different species have found that only one or a few individuals (high triggering fish; HTF) in a group account for the majority of the trigger actuations and these individuals may deviate from the group mean in terms of size, social status, and/or sex. In rainbow trout (Oncorhynchus mykiss), Arctic charr (Salvelinus alpinus) and sea bass (Dicentrarchus labrax) there is a good correlation between the social rank and the number of self-feeder actuations: one or two dominant fish performed the majority of actuations (Alanärä andBrännäs 1993, 1996;Alanärä 1993, 1994;Millot et al 2008;Millot and Bégout 2009). In Arctic charr and sea bass there is a strong negative correlation between feeding demand (and/or growth rate) and brain serotonergic activity; the main neurological marker of chronic social stress in fish (Alanärä et al 1998;Di-Poï et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This diurnal/nocturnal behaviour of sea bass has been described in relation to seasonal variations in photoperiod and water temperature (Bégout Anras 1995), sudden changes in environmental conditions (Anthouard et al 1993;Sánchez-Vázquez et al 1995b) and several intrinsic factors such as motivational level, and visual (Bardach and Todd 1970) and social stimuli ). Among the studies cited above, many used on-demand feeding systems but the relative individual contribution to feed demand was seldom investigated (Covès et al 2006;Di-Poi et al 2008;Millot et al 2008). It has however been pointed out that individual roles could direct group feeding under environmentally controlled conditions (Millot et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This is a further testimony of the limits of the ballotini technique, which is performing, but invasive, since it requires fish capture and anesthesia, so only snapshots of food intake can be obtained. These might not be representative of the actual food intake of fish over a period of time, especially if fish behavior changes between successive days or weeks (for seabass, see Millot et al, 2008). Furthermore, each snapshot was taken at a particular time of the day, and it is known that feeding rhythms or food intakes vary between times of the day, depending on the status of individual fishes in the dominance hierarchy and their motivation to feed, depending, among others, on the time elapsed since the last meal (e.g.…”
Section: Relevance Of the Hypothesesmentioning
confidence: 99%
“…The ballotini methodology ) is accurate, but it can be -E-mail: Campeasarnaud@yahoo.fr 1299 deployed on a discontinuous basis only, since it requires fish capture and deep anesthesia for X-ray analysis. Food intake can vary between times of the day or between consecutive days (Kadri et al, 1997a and1997b;Millot et al, 2008), so it is uncertain whether the pictures obtained from X-ray analyses are representative of the actual between-fish variations of food intake over a period of time. Behavioral studies have been done to bridge this gap, since behavior can be measured continuously, e.g.…”
Section: Introductionmentioning
confidence: 99%